NILAI-NILAI PENDIDIKAN AKHLAK DALAM PERSPEKTIF AZ-ZARNUJI: (Studi Atas Kitab Ta’lîm Al-Muta’allim Tharîq At-Ta’allum) - Acip Acip; Khaerunisa (STAI Pelabuhan Ratu, 2022)
Moral education is very important to be encouraged because it is part of religion, especially at this time the phenomenon of the decline in student morals is very visible and clear which illustrates the failure of the educational process in schools, the lack of role of moral education in the family and the indifferent attitude of some people so that a generation with mentality is born. thugs, irresponsible etc. This study aims to describe the values ​​of moral education in Az-Zarnuji's perspective which is contained in his work in the field of morals, namely the book Ta'lîm Al-Muta'allim Tharîq At-Ta'allum which is the teaching material for students in traditional Islamic boarding schools in Indonesia. Indonesia. The method used in this research is descriptive qualitative research type research library with historical and philosophical approaches. The results of the study show that the book of ta'limul muta'allim explains all aspects of morality, namely (1). Student morality towards God. (2). Students' morals towards themselves, (3). Morals of students towards teachers, (4). Student morals towards parents, (5). Student behavior towards friends, (6). Student morality towards science, (7). Student behavior when studying.